Protocol for the safety and efficacy of fecal microbiota transplantation liquid in children with autism spectrum disorder: a randomized controlled study - Wei, Jinying; Chen, Jiayi; Fang, Xiaohui; Liu, Tianyu; Yuan, Yanhan; Zhang, Jinping (Frontiers in Microbiology, 2023)
Background: Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by deficits in social interaction, repetitive behavior and language impairment, and its worldwide prevalence has been found to be increasing annually in recent years. Till now, ASD is uncurable as its pathogenesis remains unknown. However, studies on both animals and humans have demonstrated that fecal microbiota transplantation (FMT) may ameliorate the symptoms of ASD, as well as gastrointestinal symptoms. Nonetheless, there is still no agreement regarding the optimal dosage or duration of FMT treatment for individuals with ASD.Methods: This clinical study is a double-blind, randomized, interventional trial conducted at a single center. The aim is to investigate the safety and efficacy of a pediatric formulation of FMT for ASD. A total of 42 children between the ages of 3-9 with ASD will be randomly assigned in a 2:1 ratio to either an FMT treatment group (n=28) or a placebo group (n=14), forming cohort 1. Additionally, 30 healthy children of similar age and gender will be recruited as the control group (cohort 2). Cohort 1 will be assessed using a variety of scales, including the Autism Behavior Checklist, Childhood Autism Rating Scale, Social Responsiveness Scale, Gastrointestinal Symptom Rating This is a provisional file, not the final typeset article Scale, Children's Sleep Habits Questionnaire, and Psychoeducational Profile (Third Edition). These assessments will evaluate the effectiveness of FMT in reducing core symptoms and comorbidities (such as gastrointestinal symptoms and sleep disturbances) in children with ASD. The study will use metagenomic and metabolomic sequencing to assess changes in the composition and structure of the intestinal flora and its metabolites in blood, urine, and feces following treatment. Furthermore, the study will evaluate the acceptability of the FMT formulation by participants' legal guardians and investigate differences in the intestinal flora and metabolism in the FMT group before and after treatment compared to 30 healthy children.